Anomali Kewenangan LPKSM dalam Mengajukan Gugatan Perlindungan Konsumen di Indonesia - Zulhidayat, Muhammad (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2023)
Consumer protection is a crucial element in the concept of the rule of law in countries like Indonesia. Regulations regarding consumer protection are outlined in Law No. 8 of 1999 on Consumer Protection, along with Government Regulation No. 89 of 2019, which amends Government Regulation No. 59 of 2001 on Consumer Protection Organizations (Lembaga Perlindungan Konsumen Swadaya Masyarakat - LPKSM). Indonesia has established LPKSM as a non-governmental organization tasked with providing consumer protection services to the public. This institution is granted various powers through the Consumer Protection Act (UUPK). However, the issue arises regarding the authority of LPKSM to file lawsuits in court related to consumer protection. This research utilizes a normative legal research method. The findings reveal that the role of LPKSM in advocacy is not clearly defined, particularly whether it involves providing legal services similar to those of an advocate in court. However, based on the provisions in the Government Regulation regarding LPKSM, its role is limited to assisting consumers in filing complaints, as legal services are only provided to those who are legally qualified as advocates, as stated in Article 1, Paragraph 2 of Law No. 18 of 2003 on Advocates.